2018
DOI: 10.1074/mcp.ra117.000069
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Aspergillus fumigatus Conidia-containing Phagolysosomes Identifies Processes Governing Immune Evasion

Abstract: Invasive infections by the human pathogenic fungus Aspergillus fumigatus start with the outgrowth of asexual, airborne spores (conidia) into the lung tissue of immunocompromised patients. The resident alveolar macrophages phagocytose conidia, which end up in phagolysosomes. However, A. fumigatus conidia resist phagocytic degradation to a certain degree. This is mainly attributable to the pigment 1,8-dihydroxynaphthalene (DHN) melanin located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 64 publications
9
32
0
Order By: Relevance
“…Although trained immunity induced by melanin has not been explored, we provide evidence that this pigment is endowed with the ability to regulate mTOR and HIF-1α signaling. Our findings are supported by proteomics of conidia-containing phagolysosomes 55 , in which melanin was revealed as a major regulator of mTOR activator/regulator (LAMTOR), a member of the Ragulator/LAMTOR complex known to regulate mTOR 56 . Importantly, mTOR suppresses factor inhibiting HIF-1 (FIH-1), a negative regulator of HIF-1α 57 , and FIH-1 may represent one central node congregating mTOR and HIF-1α signaling towards the activation of glycolysis in response to infection.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although trained immunity induced by melanin has not been explored, we provide evidence that this pigment is endowed with the ability to regulate mTOR and HIF-1α signaling. Our findings are supported by proteomics of conidia-containing phagolysosomes 55 , in which melanin was revealed as a major regulator of mTOR activator/regulator (LAMTOR), a member of the Ragulator/LAMTOR complex known to regulate mTOR 56 . Importantly, mTOR suppresses factor inhibiting HIF-1 (FIH-1), a negative regulator of HIF-1α 57 , and FIH-1 may represent one central node congregating mTOR and HIF-1α signaling towards the activation of glycolysis in response to infection.…”
Section: Discussionsupporting
confidence: 65%
“…Phagosome and entotic vacuole fission depend on mTOR localization to vacuolar membranes surrounding engulfed cells 62 and, likewise, we propose that the subcellular redistribution of mTOR to melanin-containing phagosomes is required for its activation. Because the spatial organization of mTOR is coordinated through a variety of sensors and regulators that converge on Rag GTPases 63 , the phagosomal regulation of LAMTOR by melanin 55 suggests similar mechanisms during fungal infection, in line with the ability of melanized conidia to inhibit phagosomal recruitment of CaM, and prevent the specialized autophagy pathway LC3-associated phagocytosis (LAP) 43 . By deploying melanin, the fungus promotes calcium sequestration inside the phagosome and inhibits the recruitment of LAPosome machinery components, including the NADPH oxidase and CaM, to block LAP and avoid elimination 43,47 .…”
Section: Discussionmentioning
confidence: 99%
“…In line, we previously reported that dihydroxynaphthalene (DHN) melanin of conidia (spores) of the important pathogenic fungus Aspergillus fumigatus that is predicted to cause more than 200.000 life-threatening infections worldwide (Brown, Denning et al, 2012, Kosmidis & Denning, 2015, is responsible for establishing a non-hostile intracellular niche inside phagocytes by inhibiting phagolysosomal acidification, and as a consequence killing of conidia, LAP and apoptosis of phagocytes (Akoumianaki, Kyrmizi et al, 2016, Heinekamp, Thywissen et al, 2012, Schmidt, Vlaic et al, 2018, Thywissen, Heinekamp et al, 2011, Volling, Thywissen et al, 2011.…”
Section: Introductionmentioning
confidence: 91%
“…Proteins on the surface mediate direct contacts between pathogens and hosts. In addition to several known surface proteins, such as RodA, CalA, Asp f 2, and CcpA (10,12,16,19), abundant surface proteins detected in this study, such as Tef1, ArtA, Hsp70, and Hsp90, also have the potential to interact with a range of host proteins (44). Candida albicans Tef1 was shown to be surface localized and to be able to bind human Table 5), including the results obtained in this study (CEA10 B, corresponding to all the morphotypes of CEA10 obtained using the biotinylation method); the surfome of CEA10 (CEA10 T, corresponding to all the morphotypes of CEA10 obtained using the trypsin-shaving method); D141 (dormant and swollen conidia) results obtained using the trypsin shaving method (10,11); the CEA17ΔakuB KU80 dormant conidia surfome results obtained using the formic acid extract (9); and the ATCC 46645 surfome detected by hydrogen fluoride-pyridine extraction and trypsin shaving (10).…”
Section: Discussionmentioning
confidence: 83%
“…C. albicans Hsp70 protein Ssa1 is an invasin that binds to host cell cadherins to induce host cell endocytosis, which is critical for C. albicans to cause maximal host cell damage (51). In line with this, A. fumigatus Hsp70 and Hsp90 were predicted to interact with host proteins in conidia containing mouse macrophage phagolysosomes (44), suggesting the potential roles of surface HSPs in manipulating the host immune responses.…”
Section: Discussionmentioning
confidence: 84%